Demand Composition and Income Distribution - Pothier, David (IMF Working Papers; Working Paper ;, 2014)
This paper highlights how changes in the composition of demand affect income dispersion in the short run. We first document how the share of aggregate spending dedicated to labour-intensive goods and services shrinks (expands) during downturns (booms), and argue that this contributes to the observed pro-cyclicality of employment and output in labour-intensive industries. Using a two-sector general equilibrium model, we then assess how this demand composition channel influences the cyclical properties of the income distribution. Consistent with empirical evidence, we find income inequality to be countercyclical due to changes in the level of employment and (to a lesser extent) relative factor prices. The model also shows that wealth redistribution policies can potentially involve a trade-off between equality and output, depending on how they affect the composition of aggregate demand.